2021
DOI: 10.1590/1517-8692202127022020_0015
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Analysis of the Influence of Sports Dance Based on Wireless Network Mode on College Students’ Mental Health

Abstract: Sports dance can not only improve the quality of students, but also affect the healthy psychology of college students. The influence of sports dance on the mental health of college students based on the wireless network mode is investigated and analyzed. The influence of sports dance on students’ mental health quality was studied by comparing before and after the experiment. First, based on the characteristics of the wireless network mode, the MQVA algorithm based on the wireless network mode is proposed. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Self-satisfaction ↑ Wang,2019 [ 31 ] N = 90 College student 20–22 unknow Latin dance 8 weeks 2 times/week RCT PA, flexibility ↑ Soltero,2020 [ 9 ] N = 20 Breast cancer survivors (BCS) 25–75 unknow Latin dance and Tai Chi 8 weeks unknow RCT body fat overall ↓ Sofianidis,2017 [ 14 ] N = 36 older adults 65–75 10 M 26 F Latin dance and Pilates 12 weeks 2 times/week RCT Balance ↑ Romero,2012 [ 32 ] N = 73 Grade 6–9 middle school student 11–16 32 M, 41 F Latin dance 5 weeks 2 times/week RCT Self-efficacy↑; social connection ↑ Rios,2015 [ 33 ] N = 40 Parkinson’s disease. 60–65 22 M 18 F Tango dance 12 weeks 2 times/week RCT Motor and non-motor manifestations↑ Qi,2021 [ 34 ] N = 60 College student 18–23 unknow Sports dance 10 weeks unknow ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-satisfaction ↑ Wang,2019 [ 31 ] N = 90 College student 20–22 unknow Latin dance 8 weeks 2 times/week RCT PA, flexibility ↑ Soltero,2020 [ 9 ] N = 20 Breast cancer survivors (BCS) 25–75 unknow Latin dance and Tai Chi 8 weeks unknow RCT body fat overall ↓ Sofianidis,2017 [ 14 ] N = 36 older adults 65–75 10 M 26 F Latin dance and Pilates 12 weeks 2 times/week RCT Balance ↑ Romero,2012 [ 32 ] N = 73 Grade 6–9 middle school student 11–16 32 M, 41 F Latin dance 5 weeks 2 times/week RCT Self-efficacy↑; social connection ↑ Rios,2015 [ 33 ] N = 40 Parkinson’s disease. 60–65 22 M 18 F Tango dance 12 weeks 2 times/week RCT Motor and non-motor manifestations↑ Qi,2021 [ 34 ] N = 60 College student 18–23 unknow Sports dance 10 weeks unknow ...…”
Section: Resultsmentioning
confidence: 99%
“…Three studies have demonstrated that Latin dance interventions can improve cognitive function. Among them, a 10-week Latin dance intervention for college students aged 18–23 showed improvements in motivation, cognitive ability, attitude and behavior [ 34 ]. The other two studies [ 36 , 44 ] were Latin dance intervention for the older adults for 16 weeks, and the results both confirmed that Latin dance intervention can improve the physical function and cognitive function of the elderly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dancing is one of the promising types of physical activity. The importance of sports dances in health-improving activities is emphasized [2,21,22]. Dancing is considered a type of organized leisure that can be used to improve the health of the population.…”
Section: Review Articlementioning
confidence: 99%
“…Sports dancing can not only improve the quality of life, but also affect the health of young people. Qi [21] researched and analyzed the impact of sports dancing on the mental health of college students. It is shown that sports dance has a positive effect on the mental health of students.…”
Section: Review Articlementioning
confidence: 99%